PEMBINAAN PEMBELAJARAN DARING SELAMA PANDEMI COVID 19 Di SMK PERMATA HARAPAN BATAM - Hermaya Ompusunggu; Anggun Permata Husda; Elsya Paskaria Loyda Tarigan; Argo Putra Prima (ASOSIASI IDEBAHASA KEPRI, 2022)
This service aims to provide online learning guidance during the COVID-19 pandemic which was carried out at the Permata Harapan Vocational School in Batam. This training was carried out for 4 meetings using the zoom application. Community service activities in the form of educational development for Permata Harapan Vocational High School students can provide benefits by applying the methods of implementing training activities, discussions and questions and answers. This service was attended by Mr. Miftahul Ilmi and Mrs. Lolita as teachers at Permata Harapan school and also attended by 20 students. The results obtained from this activity are: the ability of students to the digital world increases, especially for the applications used and the available tools. Students also feel they have a high curiosity to understand the applications used and are interested in the menus offered. The ability to adapt to the online learning system is very necessary for current conditions, where the presenter also conveys motivation to students to continue to be able to follow the lesson well.